KARAKTERISTIK PASIEN HEMOPTISIS POST TUBERKULOSIS PARU DI POLIKLINIK PARU RSUD DR. SOEDARSO PONTIANAK - ., Bahtiar Rosyada (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Hemoptysis is coughing up blood from respiratory tract. Thecomplications are hemodynamic instability, aspiration, airway blockade,hipoxemia, and death. Tuberculosis of lung and post tuberculosis arebecome most frequent cause of hemoptysis. Patients’ visits of hemoptysisin Pulmonology clinic of Dr.Soedarso General Hospital Pontianak reach to8,1% from total visits on 2012. Objective. To find out the characteristics of post tuberculosis hemoptysis patients in Pulmonology clinic ofDr.Soedarso General Hospital Pontianak. Method. This was a descriptivestudy with cross sectional design which was conducted at Dr.SoedarsoGeneral Hospital Pontianak. There are 77 samples which were chosenwith consecutive sampling technique based on inclusion and exclusioncriteria. Samples were examined retrospectively by searching details ofpatients’ medication from medical record. The results were described withSPSS 20.0 program. Result. This research found the prevalence of posttuberculosis hemoptysis on 2008 - 2013 that reached 14,05% fromhemoptysis patients. The average of patients’ age is 50,88 ± 13 years,ranged between 26 – 82 years with male – female percentages was55,8% and 44,2%. Most patients are in age between 51 – 60 years.Another disease in the patients were bronchiectasis (50,6%), hypertension (7,8%), diabetes mellitus (3,9%), bronchitis (5,2%), Cystic Fibrosis (1,3%),Post Tubercular Obstructive Syndrome (3,9%) and unknown in 35,1 %patients.The frequencies of medication were done one time in 35 patients(45,5%) and more than one time medication in 42 patients (54,5%).Conclusion. Post Tuberculosis Hemoptysis is more suffered by men. Halfof post tuberculosis hemoptysis patients have bronchiectasis, as mostfrequent comorbidity. More than half of patients had ever taken medicationat least twice or have hemoptysis recurrency.Keyword : Hemoptysis, Post Tuberculosis, Characteristics